(untitled) (Journal of the College of Education for Women, 2025)
The study aims to explore the meaninglessness of life in Jojo Moyes’ novel "Me Before You" the profound theme of the meaninglessness of life through the poignant and complex relationship between its two central characters, Louisa Clark and Will Traynor. The story delves into the existential questions surrounding the value of life, the consequences of personal choices, and the moral dilemmas associated with assisted suicide. Moyes skillfully weaves a narrative that underscores the importance of human connections, empathy, and the potential for personal growth even in the face of seemingly insurmountable obstacles. "Me Before You" ultimately challenges readers to reflect on the fragility of life, the role of love in finding purpose, and the moral dilemmas that arise when one’s autonomy clashes with societal norms.